Controlling the mechanical properties and corrosion behavior of biomedical TiZrNb alloys by combining recrystallization and spinodal decomposition. (30th May 2022) - Ji, Pengfei; Chen, Bohan; Liu, Shuguang; Li, Bo; Xia, Chaoqun; Zhang, Xinyu; Ma, Mingzhen; Liu, Riping
Highlights: Spinodal decomposition results in abnormal effects on the mechanical properties of the alloy. Nanoprecipitates formed via spinodal decomposition hinder the movement of dislocations. The high atomic density improves the corrosion resistance and stability of passivation film. TZN-800 alloy has excellent comprehensive properties. Abstract: Excellent comprehensive mechanical properties and corrosion resistance of TiZrNb equiatomic ratio medium-entropy alloy were obtained through recrystallization and spinodal decomposition. In addition to solid solution strengthening and recrystallization, the excellent mechanical properties can also be attributed to the hindering effect of nanoprecipitation formed via spinodal decomposition on the movement of dislocations. The high atomic arrangement density due to spinodal decomposition reduces the surface energy of the alloy passivation film, thereby increasing the activation energy of dissolution and the bonding energy between atoms, which improve the corrosion resistance and stability of the alloy passivation film. This work provides a new strategy to control the mechanical properties and corrosion resistance by combining recrystallization and spinodal decomposition.